This** preview**
has intentionally

**sections.**

*blurred***to view the full version.**

*Sign up*
**Unformatted text preview: **nx n-sin nx n 3 2 x cos nx n 2-2 sin nx n 3 a n = 2 π ± π f ( x ) cos nx dx = 2 π ² ± π/ 2 f ( x ) cos nx dx + ± π π/ 2 f ( x ) cos nx dx ³ = 2 π ² ± π/ 2 x 2 cos nx dx + ± π π/ 2 π 2 4 cos nx dx ³ = 2 π ² ´ x 2 sin nx n + 2 x cos nx n 2-2 sin nx n 3 µ ¶ ¶ ¶ ¶ π/ 2 + π 2 4 sin nx n ¶ ¶ ¶ ¶ π π/ 2 ³ = 2 π ´´ π 2 4 n sin nπ 2 + π n 2 cos nπ 2-2 n 3 sin nπ 2 µ-(0 + 0-0) + π 2 4 ´-1 n sin nπ 2 µ = 2 n 2 cos nπ 2-4 πn 3 sin nπ 2 = (-1) n/ 2 2 n 2 n even (-1) ( n +1) / 2 4 πn 3 n odd f ( x ) = π 6-4 π 1 3 cos x + 2 2 2 cos 2 x + 4 π 3 3 cos 3 x-2 4 2 cos 4 x-4 π 5 3 cos 5 x + 2 6 2 cos 6 x + . . ....

View
Full Document

- Spring '08
- Bellenot
- Math, Fourier Series, Cos, Shawn Ashmore